Analysis of resource management in complex work systems : using the example of Sterile Goods Management in hospitals - Lin, Qinglian (Springer Nature, 2016)
This book develops and assesses a decision-making model for resource management in complex work systems in line with the "Systems Engineering" method. It applies the Balanced Scorecard to the development of the criteria system for decision-making, and employs fuzzy linguistics theory to evaluate the alternatives. Further, the book assesses the application of this model in a hospital that has to decide whether or not to outsource its sterile goods. The use of the model opens up a diverse range of fields for decision-making in the area of complex work systems.